The speech Act of Apology in Iraqi Arabic: A Socio-pragmatic Study - Mohammed Taher Jasim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The current research is a study of the number of occurrence, classification, and sequence of apology as a speech act in Iraqi Arabic. The examination depends on a set of 550 natural apology interactions obtained by ethnographic observation method. The findings indicated that  the obvious utterance of apology with a 'demand for forgiveness'اسف('fwan)[1] (sorry) was the most frequent apology speech act in Iraqi Arabic  and the above token with 'confession of being guilty' constituted the common set of apologies in Iraqi Arabic.  The study also indicated that the same combination of apology speech acts utilized in other examined languages ​​was frequent in Iraqi Arabic; however, the tendencies for employing these speech acts seem to be culturally dependent.[1]see appendix (1) for transcription and glossing of Arabic characters.